(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
SOMMARIO: 1. Dalla bioetica alla biogiuridica. - 2. Etica e diritto. - 3. Profili di diritto ecclesiastico nella dimensione bioetica. - 4. Questioni bioetiche e valori costituzionali. Juridical horizons of the bioethical dimension Abstract: In his broad cultural, legal and academic experience, Giuseppe Dalla Torre has also dealt with issues relating to bioethics and biolaw. His thought contribution on the subject has proved to be of great scientific importance both because from a temporal point of view he was one of the first Italian jurists to take an interest in bioethics; and because he has indicated criteria and solutions that have profoundly crossed the dynamics characterizing the debate and studies of the bioethical phenomenon in Italy. The paper intends to testify to the continuing relevance of the fundamental contents of his teaching in the bioethical sector, highlighting that they have accompanied the evolution of Italian biolaw from the very first steps.